(Ⅰ)F(x)=f(x)+g(x)=xlnx+
x2+1 2
,1 2
F′(x)=1+lnx+x,
则F(1)=1,F′(1)=2,
∴F(x)图象在x=1处的切线方程为y-1=2(x-1),
即2x-y-1=0;
(Ⅱ)令G(x)=ef(x)?g(x)=exlnx?
x2?1 2
,1 2
则G′(x)=exlnx(1+lnx)-x,
∴G″(x)=exlnx(1+lnx)2+exlnx?
?1=exlnx(1+lnx)2+e(x?1)lnx?1,1 x
∵x-1与lnx同号,
∴(x-1)lnx≥0,
∴e(x-1)lnx-1≥0
∴G′′(x)>0,
∴G′(x)在(0,+∞)单调递增,
又G′(1)=0,∴当x∈(0,1)时,G′(1)<0;当x∈(1,+∞)时,G′(1)>0.
∴G(x)在(0,1)单调递减,在(1,+∞)单调递增,
∴G(x)min=G(1)=0.
∴G(x)≥0,即ef(x)≥g(x)对任意的x∈(0,+∞)恒成立;
(Ⅲ)由(Ⅱ)知xx≥
x2+1 2
,1 2
则
+(b+c)2
aa+1
+(c+a)2
bb+1
≤(a+b)2
cc+1
+(b+c)2
a2+1 2
3 2
+(c+a)2
b2+1 2
3 2
(a+b)2
c2+1 2
3 2
=2[
+(b+c)2 2a2+b2+c2
(c+a)2
a2+2b2